Dokazování v daňovém řízení - Vrbacký, Tomáš (2007)
The diploma paper concerning the proofs in tax proceeding deals with general characteristics of tax proceeding, basic definitions, institutions and rules of tax proceedings according to current valid regulations and coherent practices of the court as well as analysis of particular proper evidences. Introduction of this diploma paper shows the importance of tax administration in relation to the state budget, the relation of first republic regulations to the currents ones, and the importance of introduction of administrative justice to the law in the Czech Republic.